Maternal dietary intake of folate, vitamin B(12) and MTHFR 677C>T genotype: their impact on newborn’s anthropometric parameters - Torres-Sánchez, Luisa (Springer Berlin Heidelberg, 2014)
In this study, we evaluated the effects of dietary intake of vitamin B(12) and folate during pregnancy and their interactions with maternal polymorphism of MTHFR (677C>T; 1298A>C) on intrauterine development. Anthropometric parameters were obtained from 231 newborns that belong to a prospective birth cohort in Morelos, Mexico. Maternal dietary intake of vitamin B(12) and folate was assessed using a semi-quantitative questionnaire administered during the first and third trimesters of the pregnancy. Maternal MTHFR 677C>T and 1298 A>C genotypes were determined by PCR–RFLP. The associations between deficient dietary intake of vitamin B(12) (<2.0 μg/d) and folate (<400 μg/d) in the first and third trimesters and maternal polymorphisms of MTHFR on anthropometric parameters at birth were estimated using a multivariate linear regression model. During pregnancy, the deficient dietary intake was roughly 60 % for folate and 19 % for vitamin B(12). Allelic frequencies of 677T and 1298C were 59 and 10 %, respectively. After adjusting for confounders, deficiency in maternal dietary intake of vitamin B(12) (<2.0 μg/d) was associated with a significant reduction in length (β ~ −2.4; 95 % CI −4.3; −0.6) and length-for-age at birth (β ~ −1.2; 95 % CI −2.3; −0.1) among infants whose mothers were carriers of the 677TT genotype (p for interaction = 0.02). In contrast, no association was observed between deficiency in maternal dietary intake of folate (<400 μg/d) and any anthropometric parameter of newborns. These results suggest that supplementation with vitamin B(12) during pregnancy could have a favorable impact on intrauterine fetal development mainly in populations that are genetically susceptible.